Faktor-Faktor Risiko yang Berhubungan dengan Kelelahan Kerja Pada Pekerja PT X - Jessica Gabriella Budi Santosa (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Work fatigue in the pharmaceutical sector is a condition that needs to be treated. In Indonesia, on average, there are 414 work accidents every day, 27.8% are caused by quite high fatigue, approximately 9.5% or 39 people experience physical disabilities due to exposure to chemical, physical, biological and other hazards. The aim of the research to be conducted is to determine the factors associated with work fatigue in the pharmaceutical sector. This type of research is quantitative research with a cross sectional research design with a sample of 60 respondents. The sampling technique used is simple random sampling. The instruments used were questionnaires and interviews, weight and height weighing tools to determine nutritional status, oymeters to measure workload, and PVT application tools used to measure the level of work fatigue carried out on respondents at PT X. The data analysis used was chi-square test. Univariate results: old age, namely 39 people (65%), obesity nutritional status, namely 30 people (50%), female gender, namely 45 people (75%), no history of disease, 58 people (96.7%), long working period namely 45 people (75%), heavy workload, namely 19 people (31.7%), night shift work, namely 22 people (36.7%), heavy work fatigue, namely 28 people (46.7%). Bivariate analysis shows that there is a relationship with each variable if p<0.05, which from the research shows that the variables age, nutritional status, work period, workload, work shifts have a positive relationship with work fatigue.